TAX REFORM IN QUÉBEC: AN ALTERNATIVE VISION - Boadway, Robin; Tremblay, Jean-François (L'Actualité économique, 2017)
Recent evidence indicates that income and wealth inequality have been increasing, while the tax-transfer system has not responded. If anything, progressivity has decreased and capital income has become increasingly sheltered. Arguably, a significant amount of the increase in inequality reflects windfall gains or rents to various taxpayers, both individuals and firms. Recent proposals by the Mirrlees Review, drawing on lessons from optimal tax analysis, include some ways that the tax system can be reformed to tax windfall gains, albeit in a context limited by distribution-neutrality. We propose a tax reform agenda for Québec and Canada that can both improve efficiency and fairness. Our proposals contrast with those of the Québec Taxation Review Committee.In our view, there is a strong case for taxing capital income as part of redistribution policy, in part because capital income includes unexpected gains, or rents, that accrue disproportionately to high-income persons. Our preferred treatment of capital income at the personal level would include the following. First, strict limits on tax sheltering should be maintained to ensure that some capital income is taxable for high-income persons. Contribution limits should be more generous for RRSPs than for TFSAs given that unexpected returns are taxed under the former but exempted under the latter. Second, capital gains on housing, above some lifetime exemption level, should be taxed. Third, a tax on large inheritances should be introduced to reduce the intergenerational transmission of wealth inequality and promote equality of opportunity.At the corporate level, we recommend a fundamental change in the role that the system is meant to play. The current system, which is designed to serve as a withholding device for the personal tax by taxing shareholder income at source, should be replaced by a cash-flow tax system, or equivalently a rent-based corporate tax. This recommendation is motivated by the fact that the corporate tax on normal risk-adjusted return is largely shifted to labour given the high degree of international capital mobility. Moreover, the withholding role of the corporate tax has become unnecessary given that most capital income is now sheltered from the personal tax. Among the different cash-flow equivalent taxes available, the allowance for corporate equity tax would be the easiest to implement. It would simply involve adding a deduction for the cost of equity finance at the risk-free interest rate in addition to the deductions for interest and depreciation that currently exist. The adoption of a cash-flow equivalent tax would mitigate the disincentives for investment, innovation and growth that the current system imposes. As well, it would eliminate the incentive to finance investment by debt.In addition, we argue that the integration of the personal and corporate income taxes has become largely unnecessary. Therefore, we recommend eliminating the dividend tax credit and the preferential treatment of capital gains. Doing so would also offset the revenue cost of adopting a rent-based corporate tax.The same tax base should apply to incorporated and unincorporated businesses. The small business deduction should be maintained, given that it compensates for the imperfect refundability of tax losses for bankrupt firms. However, cumulative lifetime limits should be adopted so firms are not rewarded for staying small.Increased income inequality calls for more progressivity of the tax system both at the top and bottom of the income distribution. This could be achieved by adding a new tax bracket for the top decile of taxpayers and making all tax credits refundable.To maintain some harmonization, these reforms should ideally be adopted by both orders of government. However, several proposals could be adopted unilaterally by the Québec government with relatively little difficulty.